Kompetensi Konselor terhadap Konseling Indigenous di Indonesia: Systematic Literature Review - Sabila, Novira Silmi; Basuki, Agus; Wulandari, Annisa Silvia; Subhan, Nurul Izzah (Universitas Muhammadiyah Metro, 2024)
Guidance and counseling play an important role in multicultural counseling, namely understanding the client's culture. Indigenous is one aspect of culture that is trusted in each region. The aim of this research is to understand various cultures in Indonesia by relating that counselors are required to have the competence to understand clients who have various backgrounds and different cultural beliefs in order to be able to carry out counseling services in accordance with the planned objectives. The method used is a systematic literature review by collecting data about culture in Indonesia. The journals collected were 12 journals related to the title, obtained from Google Scholar, Research Gate, Garuda, and Science Direct. The results of the research are the importance of counselors having multicultural competence in dealing with clients who have different backgrounds. The counselor's role is to provide services to the counselee to achieve therapeutic goals by applying the cultural values of the counselee's environment.